Pseudothrombotic appearance on pulmonary valve by intracardiac echocardiography during atrial fibrillation ablation - Sano, Makoto (J Arrhythm, 2020)
We report a case with a thrombus‐like image on pulmonary valve detected by intracardiac echocardiography before transseptal puncture for atrial fibrillation (AF) ablation. The multimodality assessment provided diagnosis of the imaging artifact and exclusion from the harmful mass. This finding could be useful for a safety management of AF ablation and avoidance of an unnecessary interruption of the procedure. [Image: see text]